Unraveling the Mind-Gut Connection: Investigating Anxiety and Depression in Functional Dyspepsia: Anxiety and Depression in Functional Dyspepsia - Saeed, Ammarah; Rabbani, Bushra; Ahmed, Adeel; Kamran, Muhammad; Naqvi, Syed Muhammad Zufiqar Hyder; Ahmed, Jameel (Pakistan Journal of Health Sciences, 2024)
Psychological association with functional dyspepsia underscores the importance of a holistic approach to its management, addressing both physical and psychological aspects of the condition. Objective: To determine the relationship of anxiety and depression with severity of dyspepsia. Methods: A prospective cross sectional study was carried out in the Endoscopy Unit, Department of Gastroenterology, Baqai Medical Institute. All patients fulfilling the Rome III criteria for functional dyspepsia with normal endoscopy findings were included in the study, Pregnant females, patients with known diabetes, chronic kidney disease, chronic liver disease and known psychiatric illness, history of peptic ulcer disease and use of NSAIDs, steroids or alternative medicine were excluded. Severity of dyspepsia was assessed by Short Form Leeds Dyspepsia Questionnaire (SF-LDQ). Whereas hospital anxiety and depression scale (HADS) was used to assess the psychological factors. Results: A total of 223 participants were included in the study. Out of 223 participants, majority 55.6% (124) had moderate dyspepsia, followed by severe dyspepsia 26.9% (60), mild dyspepsia 12.6% (28) and very mild dyspepsia 4.9% (11). Using Hospital Anxiety And Depression Scale (HAD-S), we found that out of 223 participants, 56.5% (126) had moderate to severe anxiety and depression while 29.1% (65) had mild anxiety and depression. Conclusions: It was concluded that functional dyspepsia is clearly associated with common psychological disorders like depression and anxiety. Early recognition and timely linkage to care in such cases can considerably improve the health-related quality of life and hence decrease the global burden of this common disorder.